Perspectives on social justice when becoming a teacher-researcher in the practicum: insights from physical education teacher education - Sanches Neto, Luiz; Venâncio, Luciana; Corsino, Luciano Nascimento; Conceição, Willian Lazaretti da; Vieira, Ewerton Leonardo da Silva; Barreto, Samara Moura; Freire, Elisabete dos Santos; Filgueiras, Isabel Porto; Garbett, Dawn; Ovens, Alan (Frontiers in Education, 2023)
Understanding the role teachers must play in fostering social justice is one of many tasks student teachers learn on practicum. This self-study is a collaborative endeavour between eight Brazilian teacher-researchers who work in multiple teaching positions and settings in different regions of the country. Our assumption within the broader research scope is that being a teacher-researcher has commonalities related to social justice whether teaching in K-12 schools or higher education. We have reconfigured a collaborative, four-stage methodological approach to practitioner research. In this paper, we investigate how one teacher-researcher and university professor – Luiz, the first author – has been transforming his practice towards social justice through the self-study of teacher education practices. His initial dilemma concerned his students’ practicum experiences. Through the prompting of his co-authors and critical friends, Luiz reflected on his decisions and assumptions. He presented his analysis to the group which generated the discussion which forms the basis of this paper. The contribution this paper makes is two-fold. One is to exemplify the rigorous method we used to generate alternative perspectives through self-study. The other is to explore the impact of deeply seated social injustices on our teacher education practices.